Physiological responses of male and female swimmers in different warm-up protocols - Altan, B. K.; Odabas, I. (International Journal of Human Movement and Sports Sciences, 2024)
Swimmers undertake in-water warm-ups in the race pool ahead of the competition. The objective of this study is to examine the effects of three warm-up protocols (critical velocity (CV), kick, drill, swim (KDS), critical velocity, kick, drill, swim (CVKDS)) and a no-warm-up (NOWU) condition on heart rate (HR), blood lactate (LA), and rate of perceived exertion (RPE) during a 4x50-meter maximal mixed swimming test. Forty-two national swimmers participated on a voluntary basis (21 female and 21 male). Under their coaches' supervision, the swimmers executed the CV, KDS, CVKDS, and NOWU warm-up routines on separate days. After a period of complete rest, the swimmers completed a maximum of four 50-meter laps, each consisting of a different stroke (butterfly, backstroke, breaststroke, freestyle). End time and heart rate were measured after each lap, and swimmers were asked to rate their perceived exertion immediately after finishing the test. Lactic acid levels in the swimmers were measured during the rest periods at the first (LA1), sixth (LA6), and fifteenth (LA15) minutes. Following preliminary measurements, swimmers were separated into three groups and completed the CV, KDS, and CVKDS warm-up protocol for eight weeks at the beginning of their training. After eight weeks, the tests were repeated. Data analysis was conducted using the IBM SPSS 24.0 program with statistical significance set at p<0.05. Paired-samples t-tests, independent t-tests, one-way ANOVA, and repeated measures ANOVA tests were employed. Differences in HRbut, HRback, HRbre, HRfree and LA1, LA6, LA15 between genders were observed (p<0.05). There was also a significant difference in HRbut, HRback, HRbre, HRfree and LA1, LA6, LA15 based on warm-up protocols (p<0.05); however, no significant difference was found in RPE (p>0.05). After pre-race water warm-ups, physiological responses varied by gender among male and female swimmers.